Fabrication of PVA-chitosan-based nanofibers for phytase immobilization to enhance enzymatic activity - Kamaci, Umran Duru; Peksel, Aysegul (ELSEVIER, 2020)
In the present paper, polyvinyl alcohol (PVA)-chitosan (CS) nanofibers were fabricated by using the electrospinning method under a constant voltage (23 kV) and the distance (12 cm). Phytase was purified from cowpea seeds and it was immobilized into the PVA-CS nanofibers. The effects of the electrospinning parameters such as enzyme concentration and flow rate on the catalytic activity of the free and immobilized phytase were also studied. The fabricated nanofibers were characterized via FT-IR, SEM, and XRD techniques. PVA-CS nanofiber and phytase containing nanofiber (phytase-PVA-CS) were exhibited a homogenous morphology with an average diameter of about 43.6 +/- 13.7 and 65.3 +/- 26.0 nm and fiber diameter of nanofiber containing phytase was increased after enzyme immobilization into PVA-CS nanofiber. The optimum pH and temperature of the free and immobilized phytase were also investigated. The obtained results showed that the optimum pH and temperature values of the immobilized enzyme were shifted to higher pH and temperature values after the immobilization of phytase into PVA-CS nanofiber. According to these results of the immobilized phytase, it could be used in some industrial applications such as animal feed, agriculture, pharmaceutical area, and food industry. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Chitosan; Phytase; Cowpea seeds; Nanofibers; Enzyme; ELECTROSPUN; CELLS; Biochemistry & Molecular Biology; Chemistry; Polymer Science